2021
DOI: 10.1212/wnl.0000000000011153
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide Incidence and Prevalence of Neuromyelitis Optica

Abstract: Objective:Since the last epidemiological review of NMO/NMOSD, 22 additional studies have been conducted. We systematically review the worldwide prevalence, incidence and basic demographic characteristics of NMOSD, and provide a critical overview of studies.Methods:PubMed, Ovid Medline and EMBASE using Medical Subject Headings and keyword search terms and reference lists of retrieved articles were searched from 1999 until August 2019. We collected data on the country; region; methods of case assessment and aqua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
90
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(113 citation statements)
references
References 64 publications
6
90
0
1
Order By: Relevance
“… 1 Recent worldwide epidemiological surveys showed differences in the regional and ethnic prevalence of NMOSD and a higher prevalence in Africans and non-whites. 2 , 3 Most patients with NMOSD have a relapsing-remitting course, with an increase in the number of relapses, a decrease in the recovery rate, an increase in the degree of disability, and, eventually, severe visual or motor impairment with progression of the disease. 4 Diagnosis of NMOSD is based mainly on clinical manifestations, AQP4 antibody status in serum or cerebrospinal fluid (CSF), and manifestations in the spinal cord or optic nerve seen on magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%
“… 1 Recent worldwide epidemiological surveys showed differences in the regional and ethnic prevalence of NMOSD and a higher prevalence in Africans and non-whites. 2 , 3 Most patients with NMOSD have a relapsing-remitting course, with an increase in the number of relapses, a decrease in the recovery rate, an increase in the degree of disability, and, eventually, severe visual or motor impairment with progression of the disease. 4 Diagnosis of NMOSD is based mainly on clinical manifestations, AQP4 antibody status in serum or cerebrospinal fluid (CSF), and manifestations in the spinal cord or optic nerve seen on magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%
“…38 Asian countries have overall shown a higher prevalence of NMOSD compared to the west with prevalence ranging from 2.6 to 4.9/100 000 and incidence ranging between 0.39 and 0.6/100 000. 5 There is only one population-based study reported from India. From Mangalore in south west India, epidemiological studies revealed a prevalence of 2.6/100 000.…”
Section: Epidemiology Of Neuromyelitis Optica Spectrum Disordersmentioning
confidence: 99%
“…Global epidemiological studies suggest that it is more prevalent among non white populations. 4,5 Epidemiological studies on demyelinating disorders from India are limited. Most published reports are hospital-based reviews of medical records or from regional neurology centers.…”
mentioning
confidence: 99%
“…Neuromyelitis optica is a rare chronic inflammatory central nervous system disease characterized by monophasic or recurrent attacks of optic neuritis and transverse myelitis with poor or no recovery. [1][2][3] The term neuromyelitis optica spectrum disorder (NMOSD) was established by an international panel in 2015 to enable early diagnosis in patients with or without aquaporin-4 antibodies. 1 Motor and visual impairment, pain, and fatigue are among the most prevalent and debilitating symptoms.…”
Section: Introductionmentioning
confidence: 99%